Diversity of fungi associated with rhizosphere of healthy and diseased garlic crop - Baiq Nurul Hidayah; Nani Herawati; Ai Rosah Aisah; Nita Rizky Utami (Society for Indonesian Biodiversity, 2021)
Abstract. Hidayah BN, Herawati N, Aisah AR, Utami NR. 2021. Diversity of fungi associated with rhizosphere of healthy and diseased garlic crop. Biodiversitas 22: 1433-1440. Garlic (Allium sativum L.) is an especially important horticultural crop in Indonesia because it is used as a cooking spice and for medicines and cosmetic ingredients. It is mostly grown in irrigated highlands; however Indonesian production is only supplying at most 17.5% of domestic demand. West Nusa Tenggara (WNT) Province is one of the largest garlic-producing regions in Indonesia. Currently, garlic cultivation in WNT Province is facing a problem of root rot disease. Therefore, it is necessary to investigate the fungi associated with garlic root rot disease. Research was conducted in June – September 2018 and samples were collected from Sembalun highlands (1200 m above sea level). Seventeen fungal isolates were collected from the rhizosphere of the garlic crops and fourteen of them were identified. The fungi isolated from the rhizosphere of healthy garlic crops were from the genus Aspergillus, Penicillium, and Paecilomyces. While the fungi isolated from the rhizosphere of diseased garlic crops were from the genus Aspergillus, Penicillium, Paecilomyces, Fusarium, and Phoma. The genus Fusarium and Phoma are well known as plant pathogens.